2022
DOI: 10.3389/fmicb.2022.818793
|View full text |Cite
|
Sign up to set email alerts
|

New Developments and Opportunities of Microbiota in Treating Breast Cancers

Abstract: Despite the prevalence of breast cancer (BC), over half of BC cases are unrelated to known risk factors, which highlights the importance of uncovering more cancer-related factors. Currently, the microbiota has been proven to be a potent modulator of the tumor environment in BC, which regulates the immune balance in tumor-related networks. Through a large amount of data accumulation, the microbiota has shown many possibilities to reveal more insights into the development or control of BC. To expand the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Therefore, the production of microbiota-specific metabolites stimulated immunotherapy among patients diagnosed with melanoma. An extensive investigation in 2020 scrutinized more than seven tumor tissues, which ultimately detected distinct microbiota profiles within tumor tissue when compared to normal tissue [72]. Particularly, breast tumor tissues exhibited a substantial abundance of diverse microbiotas.…”
Section: Gut Microbiota Crosstalk With Icismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the production of microbiota-specific metabolites stimulated immunotherapy among patients diagnosed with melanoma. An extensive investigation in 2020 scrutinized more than seven tumor tissues, which ultimately detected distinct microbiota profiles within tumor tissue when compared to normal tissue [72]. Particularly, breast tumor tissues exhibited a substantial abundance of diverse microbiotas.…”
Section: Gut Microbiota Crosstalk With Icismentioning
confidence: 99%
“…Particularly, breast tumor tissues exhibited a substantial abundance of diverse microbiotas. The alterations in gut microbiota diversity primarily occur in relation to the various stages and subtypes of cancer [72]. Accordingly, specific microbiota, namely Cloacibacterium, Blastomonas, Stakelama, Filibacter, Anaerostipes, Alloprevotella, and PRD01a011B, have been identified in HER2-positive breast cancer patients, as opposed to HER2-negative tumors.…”
Section: Gut Microbiota Crosstalk With Icismentioning
confidence: 99%
“…29 The gut microbiome composition of breast cancer patients differs based on their estrogen receptor (ER) status, with patients with ER-positive breast cancer having a higher abundance of Lactobacillus and Bifidobacterium, while patients with ER-negative breast cancer had a higher abundance of Fusobacterium. 66 Some studies have observed differences in the microbial composition of specific bacterial phylotypes that have been linked to breast cancer, such as Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes, Sphingomonas yanoikuyae, and Methylobacterium radiotolerans in breast tissue between individuals with breast cancer and those without the disease 42,[67][68][69] Due to the gut microbiome's close interaction with the immune system, it has recently gained increased attention for its potential role in immunotherapy. The response rate of a patient to immunotherapy depends on immune competency, diversity, antigen specificity variation, antigen expression, and the recent identification of the role of gut microbiota.…”
Section: Potential Implications Of the Microbiome On Onco-therapeuticsmentioning
confidence: 99%
“… 29 The gut microbiome composition of breast cancer patients differs based on their estrogen receptor (ER) status, with patients with ER‐positive breast cancer having a higher abundance of Lactobacillus and Bifidobacterium , while patients with ER‐negative breast cancer had a higher abundance of Fusobacterium . 66 Some studies have observed differences in the microbial composition of specific bacterial phylotypes that have been linked to breast cancer, such as Proteobacteria , Actinobacteria , Firmicutes , Bacteroidetes , Sphingomonas yanoikuyae , and Methylobacterium radiotolerans in breast tissue between individuals with breast cancer and those without the disease 42 , 67 , 68 , 69 …”
Section: Potential Implications Of the Microbiome On Onco‐therapeuticsmentioning
confidence: 99%
“…Moreover, SCFA activates molecules involved in pathways that mediate the immunity and inflammation response in murine models [ 89 ]. The intestinal microbiota directly or indirectly acts on host tumorigenesis; thus, in previous years, postbiotics have received considerable attention as cancer adjuvant therapy [ 90 ]. Different studies have indicated that postbiotics have the ability to moderate the effectiveness of cancer treatment and to reduce the side effects of conventional cancer therapies (chemotherapy and antibiotic-induced diarrhea) that help cancer patient recovery.…”
Section: Mineral-enriched Postbiotics and Their Applications In Micro...mentioning
confidence: 99%